ANALISIS KORELASI HARGA TERHADAP WARNA DAN MUTU SENSORIS KEMPLANG IKAN GABUS (Channa striata) DI PASAR CINDE PALEMBANG - Toni Octavianus; Agus Supriadi; Siti Hanggita (Universitas Sriwijaya, 2014)
This study aims to investigate the characteristics of color and sensory quality fish crackers at some price ranges and also to determine the relationship between price and color characteristics and sensory quality fish crackers on retailers who are market at Cinde Palembang. This research was conducted at the Laboratory of Fishery Product Technology, Laboratory of Agricultural Technology Faculty of Agriculture, Laboratory of Bioprocess Engineering Chemistry Indralaya Sriwijaya University in April 2014 until May 2014. The research method in this study is a exploratory experiments, with three price categories (low, medium and high). Parameters observed are color characteristic and quality sensory (scents, color, crispness and flavor). The results showed a strong correlation in chroma, scents and flavor. As for the correlations that medium found in the color and crispness. The results of a low correlation with the level of relationship contained in lightness and hue